Development and validation of animal variant classification guidelines to objectively evaluate genetic variant pathogenicity in domestic animals - Boeykens, Fréderique; Abitbol, Marie; Anderson, Heidi; Casselman, Iris; de Citres, Caroline Dufaure; Hayward, Jessica J.; Häggström, Jens; Kittleson, Mark D.; Lepri, Elvio; Ljungvall, Ingrid; Longeri, Maria; Lyons, Leslie A.; et al. (Frontiers in Veterinary Science, 2024)
Assessing the pathogenicity of a disease-associated genetic variant in animals accurately is vital, both on a population and individual scale. At the population level, breeding decisions based on invalid DNA tests can lead to the incorrect inclusion or exclusion of animals and compromise the long-term health of a population, and at the level of the individual animal, lead to incorrect treatment and even life-ending decisions. Criteria to determine pathogenicity are not standardized, i.e., no guidelines for animal variants are available. Here, we aimed to develop and validate guidelines to be used by the community for Mendelian disorders in domestic animals to classify variants in categories based on standardized criteria. These so-called animal variant classification guidelines (AVCG) were based on those developed for humans by The American College of Medical Genetics and Genomics (ACMG). In a direct comparison, 83% of the pathogenic variants were correctly classified with ACMG, while this increased to 92% with AVCG. We described methods to develop datasets for benchmarking the criteria and identified the most optimal in silico variant effect predictor tools. As the reproducibility was high, we classified 72 known disease-associated variants in cats and 40 other disease-associated variants in eight additional species.